Perancangan Game Kartu Interaktif Berbasis Android Menggunakan Augmented Reality - Chowanda, Andry (ComTech: Computer, Mathematics and Engineering Applications, 2011)
By utilizing the augmented reality technology which now develops well, a card game system design and the game prototype are created on through this study Android-based Smartphone. This study is expected to increase the children’s interest to play cards in a modern way, to be utilized as a reference material for business actors in the world, and to be an alternative facility for marketing officers to market their products. The scope of this study is limited only to the system design and the prototype making of the game. The combination of waterfall methodology and a game design by Jesse is used in this study. From the results of the study it is concluded that the augmented reality technology is able to make the game more interesting.